Exacerbated ischemic brain damage in type 2 diabetes via methylglyoxal-mediated miR-148a-3p decline - Zhenguo Yang; Cheng Huang; Wenhui Huang; Chao Yan; Xueyi Wen; Di Hu; Hesong Xie; Kejing He; Chi Kwan Tsang; Keshen Li (BMC Medicine)
Abstract Background Although microvascular dysfunction is a widespread phenomenon in type 2 diabetes (T2D) and is recognized as a main cause of T2D-aggravated ischemic stroke injury, the underlying mechanisms by which T2D-mediated exacerbation of cerebral damage after ischemic stroke is still largely uncharacterized. Here, we found that methylglyoxal-mediated miR-148a-3p decline can trigger blood-brain barrier dysfunction, thereby exacerbating cerebrovascular injury in diabetic stroke. Methods Using T2D models generated with streptozotocin plus a high-fat diet or db/db mice, and then inducing focal ischemic stroke through middle cerebral artery occlusion and reperfusion (MCAO/R), we established a diabetic stroke mouse model. RNA-sequencing was applied to identify the differentially expressed miRNAs in peri-cerebral infarction of diabetic stroke mice. RT-qPCR confirmed the potential miRNA in the plasma of ischemic stroke patients with or without T2D. Fluorescence in situ hybridization was used to image the localization of the miRNA. Brain pathology was analyzed using magnetic resonance imaging, laser-Doppler flowmetry, and transmission electron microscope in diabetic stroke mice. Immunofluorescence and immunoblotting were performed to elucidate the molecular mechanisms. Results miR-148a-3p level was downregulated in the peri-infarct cortex of stroke mice and this downregulation was even more enhanced in diabetic stroke mice. A similar decrease in miR-148a-3p expression was also confirmed in the plasma of ischemic stroke patients with T2D compared to patients with ischemic stroke only. This miR-148a-3p downregulation intensified the severity of BBB damage, infarct size, and neurological function impairment caused by stroke. Notably, the reduction in miR-148a-3p levels was primarily triggered by methylglyoxal, a toxic byproduct of glucose metabolism commonly associated with T2D. Furthermore, methylglyoxal somewhat replicated the influence of T2D in exacerbating BBB damage and increasing infarct size caused by ischemia. Mechanistically, we found that downregulation of miR-148a-3p de-repressed SMAD2 and activated matrix metalloproteinase 9 signaling pathway, promoting blood-brain barrier impairment, and exacerbating the cerebral ischemic injury. Conclusions Blood-brain barrier damage caused by methylglyoxal-mediated miR-148a-3p downregulation may provide a novel target for the therapeutic intervention for the treatment of stroke patients with diabetes.